Oxidative Stress and Beta Amyloid in Alzheimer's Disease. Which Comes First: The Chicken or the Egg? - Elena Tamagno; Michela Guglielmotto; Valeria Vasciaveo; Massimo Tabaton (MDPI AG, 2021)
The pathogenesis of Alzheimer's disease involves β amyloid (Aβ) accumulation known to induce synaptic dysfunction and neurodegeneration. The brain's vulnerability to oxidative stress (OS) is considered a crucial detrimental factor in Alzheimer's disease. OS and Aβ are linked to each other because Aβ induces OS, and OS increases the Aβ deposition. Thus, the answer to the question "which comes first: the chicken or the egg?" remains extremely difficult. In any case, the evidence for the primary occurrence of oxidative stress in AD is attractive. Thus, evidence indicates that a long period of gradual oxidative damage accumulation precedes and results in the appearance of clinical and pathological AD symptoms, including Aβ deposition, neurofibrillary tangle formation, metabolic dysfunction, and cognitive decline. Moreover, oxidative stress plays a crucial role in the pathogenesis of many risk factors for AD. Alzheimer's disease begins many years before its symptoms, and antioxidant treatment can be an important therapeutic target for attacking the disease.